DMS2015short-2: Advanced learning technologies for eLearning in the enterprise: Design of an Educational Adventure Game to teach computer security. (December 2015) - D'Apice, Ciro; Grieco, Claudia; Piscopo, Rossella; Liscio, Luca
Abstract: Emerging requirements for learning in the enterprise are developing critical reasoning and keeping the learner engaged. Advanced didactical material that exploits gameful design should increase engagement by creating a product that has the spirit, and not just the mechanics, of a good game. This article presents game design guidelines for the development of an Educational Adventure Game and how they have been applied during the development of SIRET Security Game, a game that teaches workers the importance of following computer security policies.